Risk Factors for Normal and High-Tension Glaucoma in Poland in Connection with Polymorphisms of the Endothelial Nitric Oxide Synthase Gene - Kosior-Jarecka, Ewa (PLoS One, 2016)
AIM: The purpose of this study was to evaluate the influence of polymorphisms of the eNOS gene on the clinical status of patients with normal and high tension glaucoma. METHODS: 266 Polish Caucasian patients with primary open angle glaucoma were studied. Of the 266, 156 had normal tension glaucoma (NTG) and 110 high tension glaucoma (HTG). DNA material was isolated from peripheral venous blood using commercial kits. Real-time PCR reaction was used to amplify the promoter site of the endothelial nitric oxide synthase (eNOS) gene, including the single nucleotide polymorphism (SNP) site T-786C and part of the 7(th) exon of eNOS, including G894T SNP. Genotypes were determined with TaqMan SNP Genotyping Assays. RESULTS: There were no significant differences in frequencies of the allelic variants of both polymorphisms. In G894T SNP, however, the wild GG form was more common in the HTG group. The SNP of the eNOS gene did not significantly influence the progression rate in either of the groups studied. There were no differences in variants of the eNOS gene regarding the necessity for and success of surgery and the progression of the disease. In the NTG group, no statistical correlation was observed between G894T, T786C polymorphism variants, and risk factors such as optic disc haemorrhages, optic disc notches, and peripapillary atrophy. Mean diastolic and systolic pressure during the day and night were lowest in NTG patients with the CC variant of the T786C polymorphism. No statistical correlation was observed between the G894T and T786C polymorphisms and capillaroscopic examination results. CONCLUSIONS: Genotype frequencies are similar for both the eNOS G894T and T-786C polymorphisms in NTG and HTG patients. These polymorphisms do not correlate with risk factors and do not influence the state of the capillary system in NTG patients. Systolic blood pressure is lower in NTG patients with mutated alleles of both polymorphisms.